Respostas produtivas e comportamentais durante a ordenha de vacas Holandesas em início de lactação - De Felicio Porcionato, Marco Aurélio; Negrão, João Alberto; De Paiva, Fernanda Alves; Delgado, Thiago Ferreira Gonçalves [UNESP] (Universidade Estadual de Maringa, 2009)
Aiming to compare milk yield, residual milk and behavioral responses of Holstein cows during milking, fourteen experimental cows were mechanically milked twice a day, and evaluated during the first six weeks of lactation. Milk yield was measured daily, and residual milk volume weekly. Body (ribs region), udder and teat temperatures and respiratory frequency were measured twice a week. Animal behavior at the milking parlor was registered using ethograms and interviews with the milkers. During the first weeks of lactation, a higher percentage of kicks, over-steps, milking cups being knocked down, urinations and vocalizations in primiparous cows (p < 0.05) was observed, which were also considered more reactive by the parlors compared to multiparous cows. Multiparous cows produced more milk than primiparous (p < 0.05). However, there were no significant differences in residual milk percentage (p > 0.05), which suggests adaptation of both groups to the milking environment.
Productive and behavioral responses during milking of Holstein cows in early lactation
Keywords: Adaptation; Behavior; Milk ejection; Stress; Animalia